Pemberdayaan UMKM Kota Batu (Malang) Di Era Transformasi Bisnis Pada Industri E-Commerce - Muhammad Nasrullah; Dida Rahmadanik (Politeknik Kampar, 2023)
Economic development covers various aspects ranging from improving community welfare, poverty alleviation, social inclusion and others. This can be linked to the important role of MSMEs, which are drivers of innovation and creativity in the economic sector. This research aims to analyze the empowerment of Batu City MSMEs in facing business changes by the e-commerce industry and will discuss the challenges faced by MSMEs currently. The data in the research are the results of a focus group discussion by conducting a direct analysis survey on Batu City MSMEs. This article uses the Community Empowerment theory approach by Jim Ife.